2007
DOI: 10.1016/j.neuron.2007.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Ena/VASP Is Required for Neuritogenesis in the Developing Cortex

Abstract: Mammalian cortical development involves neuronal migration and neuritogenesis; this latter process forms the structural precursors to axons and dendrites. Elucidating the pathways that regulate the cytoskeleton to drive these processes is fundamental to our understanding of cortical development. Here we show that loss of all three murine Ena/VASP proteins, a family of actin regulatory proteins, causes neuronal ectopias, alters intralayer positioning in the cortical plate, and, surprisingly, blocks axon fiber t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
211
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(220 citation statements)
references
References 60 publications
8
211
1
Order By: Relevance
“…To determine if deletion of Ena/VASP proteins altered T-cell trafficking in vivo, we used EVL/VASP doubleknockout (dKO) mice (generously provided by Frank Gertler, Massachusetts Institute of Technology, Cambridge, MA) (31,32). We confirmed EVL and VASP deletion in T cells, and verified that Mena was not up-regulated as a compensatory mechanism in EVL/ VASP dKO T cells by Western blot analysis (Fig.…”
Section: Deletion Of Evl and Vasp Does Not Significantly Affect T-cellmentioning
confidence: 74%
“…To determine if deletion of Ena/VASP proteins altered T-cell trafficking in vivo, we used EVL/VASP doubleknockout (dKO) mice (generously provided by Frank Gertler, Massachusetts Institute of Technology, Cambridge, MA) (31,32). We confirmed EVL and VASP deletion in T cells, and verified that Mena was not up-regulated as a compensatory mechanism in EVL/ VASP dKO T cells by Western blot analysis (Fig.…”
Section: Deletion Of Evl and Vasp Does Not Significantly Affect T-cellmentioning
confidence: 74%
“…Primary hippocampal neurons and dorsal root ganglion (DRG) neurons cultured in the devices were obtained from embryonic day 14.5-16.5 mice as per protocols described in detail elsewhere 28,29,30 . Cells from micro-dissected cortices were dissociated and resuspended in serum-free media at a final concentration of 10 million cells/mL.…”
Section: Neuron Isolation and Culturementioning
confidence: 99%
“…As for the role of the actin cytoskeleton, although earlier work suggested that the actin depolymerizing drug cytochalasin D did not inhibit neurite formation in chick dorsal root ganglia neurons [40], more recent studies have demonstrated a critical role of the Ena/Mena/VASP family of proteins (abbreviated as Ena/VASP) in neurite formation [41,42]. Ena/VASP proteins regulate actin dynamics by antagonizing actin filament capping and promoting filament bundling [43,44].…”
Section: Introductionmentioning
confidence: 99%